Plant design manufacture of polyvinyl butyral - Carcellar, Cristobal L.; Esguerra, Raymundo; Pulmano, Octavio P. (Diliman, Quezon City College of Engineering, 1960)
This plant design covers the commercial production of polyvinyl butyral. Polyvinyl butyral is a kind of plastic used mainly as an interlayer in safety glasses, coatings for water-proof materials such as raincoats, raw materials in the production of other plastic commodities, etc. The total annual operating cost amounts to P30,655,680 and the total sales amounts to P36,000,000 both at maximum rate of production. The per cent return on capital investments as obtained from the break-even chart of this plant is 44.7%.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 68 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants